Reduction Cranioplasty in Macrocephaly and Its Surgical Technique - Acharya, Abhijit; Mahapatra, Ashok Kumar; Panigrahi, Souvagya; Deo, Rama Chandra; Senapati, Satya Bhusan; Samal, Rajiba Lochan; Puppala, Sumirini (Indian Journal of Neurosurgery, 2025)
Macrocephaly is a condition where the head circumference increases by more than 2 standard deviations above the normal size as per age. We present the case of a 9-year-old boy with macrocephaly due to arrested hydrocephalous. He had difficulty sitting up from a supine position and walking with a large head (62 cm). He has cosmetic disfigurement. Reduction cranioplasty was performed in two stages. There was a gross cosmetic improvement of craniofacial deformity with improvement in head holding after the second surgery. There is very limited literature describing the surgery and we have tried to describe in detail how we do it.
Keywords: macrocephaly; hydrocephalous; reduction cranioplasty